Afterword: Manufacturing Gambling. Issue 3 (November 2014) - Cassidy, Rebecca; Pickles, Anthony J
Abstract In this afterword I outline the expansion and reclassification of gambling which has been taking place over the past 30 years. Expansion has coincided with the emergence of gambling studies, which concentrates on identifying and counting pathological subjects as 'problem gamblers'. This focus on individual consumption deflects attention from broader structural questions including the redistributive effects of gambling expenditure and taxation. Ethnographic descriptions of gambling including those contained in this edition have the potential to disrupt the field of gambling studies. Firstly, by introducing a focus on relationships rather than individuals, and secondly by showing that gambling reflects diverse ideas about luck, uncertainty, wealth and personhood.